Estresse parental e uso de telas por crianças até 5 anos durante a pandemia por COVID-19 - Gomes, Clarissa Costa (2022)
The stricter social distancing strategy during the COVID-19 pandemic, although essential to contain the virus, can lead to negative outcomes in family health, including emotional and behavioral changes, such as increased use of screens. Among families with young children, the feeling of concern, uncertainty and stress influenced the forms of care, as parents and/or caregivers had to reorganize the home environment, generating new situations until then. Thus, the objective of the study was to investigate the profile of screen use by children up to 5 years old and analyze parental stress during the COVID-19 pandemic period. This was a cross-sectional study, with the application of a sociodemographic questionnaire, the profile of the family's screen use and application of the Parental Stress Scale. Data collection took place virtually through the snowball technique, through a Google Docs link, shared by social networks such as WhatsApp, Facebook and Instagram, from June to August 2021 and comprised a sample of 417 participants. Data were tabulated and later statistical analysis and association of variables were performed in the Statistical Package for the Social Sciences version 20.0. The study was approved under opinion 4,912,020. The results showed the predominance of mothers, with an average age of 32.85 years and female children, with an average of 2.7 years, with a family income of 6.54 minimum wages. The use of screens by children was 2.72 hours/day (use of television) and for parents 7.37 hours/day (predominant use of cell phones/tablets) for distracting activities. The application of the Parental Stress scale resulted in a low level of stress considered a positive point in the face of social distancing. It was evidenced that the variables: being a mother, young and with less schooling had a higher level of parental stress. It was found that children's longer screen time was significantly associated with greater parental stress (P>0.001). In the end, it was concluded that it is important to understand the dynamics of family stress and the profile of the use of screens, considering that the COVID-19 pandemic has imposed on the world new ways of experiencing family ties, requiring more child health care. directed to contemporary problems, with the nurse as one of the main agents responsible for the establishment of educational strategies that promote positive parenting.